Destructive Consequences Of Social Neuroticism And Psychological Means Of Prevention - Petrosyan, Rafik (Զանգակ հրատ.)
In psychology, the destructive development of social neuroticism, as an independent process, has been little studied. The question of what impact adverse or unregulated social relations have on the destructive development of social neuroticism has not been fully studied. In addition, special concepts that could serve as a basis for preventing the destructive impact of social neuroticism have not yet been introduced into the psychological discipline. This article presents the main forms and features of the destructive consequences of social neuroticism. Social neuroticism is characterized as a set of individual-personal qualities that are influenced by adverse processes and social relationships occurring in the social environment. Therefore, there is a need to develop methodological guidelines aimed at extinguishing the negative potential of social neuroticism for different social groups, in particular, immigrants with social alienation or marginalization, and people of different age groups in crisis stages of life.
Keywords: Psychology